Poly(iminoborane)s: An Elusive Class of Main‐Group Polymers?. Issue 42 (6th October 2016) - Ayhan, Ozan; Eckert, Thomas; Plamper, Felix A.; Helten, Holger
Abstract: The significance of inorganic main‐group polymers is demonstrated most clearly by the commercial relevance of polysiloxanes (silicones). Organoboron‐based materials such as π‐conjugated organoborane polymers and BN‐doped polycyclic aromatic hydrocarbons are currently attracting considerable attention. Surprisingly, poly(iminoborane)s (PIBs; [BRNR′] n ), that is, the parent unsaturated BN polymers, which are formally isoelectronic to polyacetylene, have not been convincingly characterized thus far. Herein, we present the synthesis and comprehensive characterization of a linear oligo(iminoborane), which comprises a chain of 12–14 BN units on average. With our synthetic approach, unwanted side reactions that result in borazine formation are effectively suppressed. Supporting DFT and TD‐DFT calculations provide deeper insight into the microstructure and the electronic structure of the oligomer. Abstract : B‐N‐B‐N‐B‐N… : Poly(iminoborane)s are elusive inorganic‐backbone polymers that are formally isoelectronic to polyacetylene. The first oligo(iminoborane) with a well‐defined microstructure was synthesized through an approach that effectively prevents the formation of unwanted cyclic products. The essentially linear oligomer adopts a helical conformation in solution. UV irradiation is associated with N→B charge transfer.